Navigating life following surgery - Quality of life in patients with supratentorial intraventricular brain tumors - Adrian Mircea Furtos; Aurelia Mihaela Sandu; Radu Mircea Gorgan; Ligia Gabriela Tataranu (Balneo and PRM Research Journal)
Intraventricular tumors are rare lesions growing inside brain ventricles. The aim of this study was to assess the quality of life of patients operated for supratentorial intraventricular tumors and identify prognostic factors for postoperative outcome. We performed an observational retrospective study, including consecutive patients operated for supratentorial intraventricular tumors, from 2009 to 2024. We found 217 patients; there were 118 (54.4%) males and 99 (45.6%) females, with mean age 44 years. We achived gross total resectionin 73.7% of cases.Favorable postoperative outcome was seen in 79.7%.Morbidity was 29.5%, and mortality was 6.5%. Endoscopy had similar results compare to open surgery. Quality of life was influenced, in bivariate analysis, by preoperative mRS, intracranial hypertension, hydrocephalus, minimally invasive surgery, histological grade, and postoperative complications, but in multivariate logistic regression, only preoperative mRS (p=0.022), intracranial hypertension (p=0.001) and postoperative complications (p=0.000) remained independent predictors. Surgery is the treatment of choice in supratentorial intraventricular brain tumors. Endoscopy is a feasible alternative to open surgery, with similar postoperative results. Outcome is favorable in most patients and quality of life is significantly influenced by preoperative mRS, presence of intracranial hypertension and postoperative complications.